Crystal Structure of 4′-Phenyl-1′,4′-Dihydro-2,2′:6′,2″-Terpyridine: An Intermediate from the Synthesis of Phenylterpyridine - Alexander Sedykh; Maksim Zhernakov; Mariia Becker; Dirk G. Kurth; Klaus Müller-Buschbaum (Crystals, 2025)
The intermediate compound 4′-phenyl-1′,4′-dihydro-2,2′:6′,2″-terpyridine (pdhtpy) was isolated for the first time during the synthesis of 4′-phenyl-2,2′:6′,2″-terpyridine (ptpy) and characterised by single-crystal X-ray diffraction. Pdhtpy crystallises in the triclinic crystal system with space group P<semantics><mover>1–</mover></semantics> with the following unit cell parameters at 100 K: a = 6.1325(4) Å; b = 8.2667(5) Å; c = 16.052(2) Å; α = 86.829(2)°; β = 82.507(2)°; γ = 84.603(2)°; V = 802.49(9) Å3. The absence of stabilising electron-withdrawing groups renders pdhtpy prone to oxidative conditions. Pdhtpy was obtained as a mixture with ptpy, confirmed by Rietveld refinement of the powder X-ray diffraction pattern. Notably, pdhtpy is the first solid-state 1,4-dihydropyridine lacking electron-withdrawing groups at both positions 3 and 5, distinguishing it from Hantzsch esters and related compounds.